RANCANG BANGUN SISTEM INFORMASI KELUHAN PADA RUSUN BP BATAM BERBASIS WEB - Yanti, Srimau; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2023)
ABSTRACT BP Batam is a government agency that manages flats in Batam City which are located at several points in each sub-district, this Batam City government program really supports low-income people because they are able to provide livable housing for flat residents at affordable prices, but there are several things that become obstacles for flat occupants, one of which is a citizen complaint information system which makes flat residents uncomfortable by submitting reports of damage that has occurred to each flat that must come to the flats office to report complaints, as well as flats. admin / staff who make a report every time there is damage. Therefore we need a system that can simplify and speed up occupants and flat workers in the process of reporting complaints, the system uses the PHP my Admin programming language and My SQL database with the prototyping method. The purpose of creating this system is to make it easier for BP Batam flat occupants to submit their complaints to the admin or flat employees. In addition to facilitating and speeding up the admin work process in reporting damage to flats managed by BP Batam.